2021
DOI: 10.3389/fpsyt.2021.736172
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors Associated With Mental Health Outcomes Among Dental Medical Staff in Emergency Exposed to Coronavirus Disease 2019: A Multicenter Cross-Sectional Study in China

Abstract: Background: The epidemic infection of coronavirus disease 2019 (COVID-19) may have a profound impact on dentistry, mainly due to the mode of transmission of the pathogen, which poses a risk to almost all dental operations. Therefore, this study aimed to investigate the prevalence and influencing factors of anxiety, depression, perceived stress, and acute stress disorder among dental medical staff in emergency situations during the COVID-19 epidemic.Methods: From April 3, 2020, to April 10, 20204, a multicenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…(2) Among the study subjects, more doctors were working in government hospitals, so there may be a deviation in the sample results. Interestingly, our study found that education level was inversely associated with stress status, which was similar to Chen et al ( 32 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(2) Among the study subjects, more doctors were working in government hospitals, so there may be a deviation in the sample results. Interestingly, our study found that education level was inversely associated with stress status, which was similar to Chen et al ( 32 ).…”
Section: Discussionsupporting
confidence: 91%
“…Perceived wellness survey (PWS) is a valid scale for researching and evaluating interventions in the field of perceived health, with good reliability and validity (14,15). The PWS contains 36 items which included six dimensions: physical (1,7,13,19,25,31), emotional (2,8,14,20,26,32), social (3,9,15,21,27,33), psychological (4,10,16,22,28,34), spiritual (5,11,17,23,29,35), and intellectual (6,12,18,24,30,36) which were selected based on the strength of theoretical support and the quality of empirical evidence supporting each. The PWS assesses the perceived health of individuals and their physical, mental, and spiritual states and the social health they exhibit through relationships with others.…”
Section: Perceived Wellness Surveymentioning
confidence: 99%
“…Many recent studies have reported similar findings regarding the psychological consequences of the COVID-19 pandemic for dental health professionals. The prevalence of anxiety among frontline dental staff was reported to be 46.4% in a study by Chen et al [ 30 ]. In another study 42.5% of dentists had COVID-19-associated anxiety and 35% of them had general health disorders [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dental care environment, which involves face-to-face communication with patients and exposure to saliva, blood, other body fluids and airborne microorganisms suspended in the air for long periods, as well as handling sharp instruments, carries the risk of contagion [ 20 ]. Moreover, working conditions, work-related stressors and the high risk of infection, as well as the fear of contagion and spread to family members, may have influenced dentists’ mental health during the COVID-19 pandemic [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dentists who reported no fear of being infected by the disease were more likely to be infected by COVID-19, which raises questions about the influence of the more or less strict preventive measures adopted by them. Moreover, the high risk of SARS-CoV-2 infection in dental offices, along with the frequent occurrence of COVID-19 among dentists’ relatives and friends, could be associated with high levels of psychosis and anxiety, 2 , 5 which may help to explain the high prevalence of use of off-label medication for COVID-19.…”
Section: Discussionmentioning
confidence: 99%